2011
DOI: 10.1007/s11434-010-4061-z
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculations of the β′-Mg7Gd precipitate in Mg-Gd binary alloys

Abstract: The metastable β′ phase is often the most effective hardening precipitate in Mg-Gd based alloys. In this paper, the structural, elastic and electronic properties of the recently identified β′-Mg 7 Gd precipitate in Mg-Gd binary alloys were investigated using first-principles calculations based on density functional theory. The lattice mismatches between the coherent β′-Mg 7 Gd precipitate and α-Mg matrix are discussed and used to rationalize the experimentally observed morphology of the precipitate. The mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…4) is the same as that of the HCP α-Mg matrix. As mentioned earlier in the Heat-treated RE-Mg Alloys section, the orientation of β′ precipitates has been verified as c-base-centred orthorhombic system, 47,54,81,83,84,86 and it was observed to form on the prismatic planes of the Mg matrix in a dense triangular arrangement. 82 Thus, the precipitate was plotted vertically to the X-axis (the basal plane of the Mg matrix) in Fig.…”
Section: Role Of Re Elements On Cyclic Deformationsupporting
confidence: 63%
See 2 more Smart Citations
“…4) is the same as that of the HCP α-Mg matrix. As mentioned earlier in the Heat-treated RE-Mg Alloys section, the orientation of β′ precipitates has been verified as c-base-centred orthorhombic system, 47,54,81,83,84,86 and it was observed to form on the prismatic planes of the Mg matrix in a dense triangular arrangement. 82 Thus, the precipitate was plotted vertically to the X-axis (the basal plane of the Mg matrix) in Fig.…”
Section: Role Of Re Elements On Cyclic Deformationsupporting
confidence: 63%
“…(Gd,Y) as reported by Gao et al 84 and Nishijima et al 85 These β′ precipitates have great ability to retard dislocation motion on the basal planes. 40,41,71,81,86 Similar precipitates were also observed in the solution-treated and aged Mg-10Gd-3Y-0.4Zr alloy by He et al, 81 solution-treated and aged Mg-15Gd-0.5Zr alloy by Gao et al, 54 and cast T6 samples of Mg-4Y-2Nd-1Gd-0.4Zr alloy by Liu et al 87…”
Section: Heat-treated Re-mg Alloysmentioning
confidence: 69%
See 1 more Smart Citation
“…Such precipitates were identified by selected area electron diffraction (SAED) analysis to be a b¢ phase which had a c-based centered orthorhombic structure (cbco) (a = 29 a a-Mg = 0.64 nm, b = 89d ð1010Þ a-Mg = 2.22 nm, c = c a-Mg = 0.52 nm). [31,59,60] The composition of b¢ phase was determined to be approximately Mg 7 (Gd,Y) as reported by Gao et al [61] and Nishijima et al [62] A similar type of precipitates has also been reported in the cast T6 samples of Mg-10Gd-2Y-0.5Zr alloy by He et al, [31] solution-treated and aged Mg-10Gd-3Y-0.4Zr alloy by He et al, [59] and solution-treated and aged Mg15Gd-0.5Zr alloy by Gao et al [60] Figure 4 shows the crystallographic textures (basal (0001), prismatic ð1010Þ, and pyramidal ð1011Þ pole figures) of the GW103K alloy in different states (asextruded, T5, and T6 conditions) evaluated using MTEX software, where ED stands for the ED and RD denotes the radial direction. As seen from Figure 4, relatively weaker textures (with a maximum intensity of 2.1 multiples of random distribution (MRD) for the asextruded, 3.3 MRD for the T5, and 4.5 MRD for the T6 samples were observed after the defocusing correction, in comparison with the extruded AM30 [14] and rolled AZ31.…”
Section: Resultsmentioning
confidence: 90%
“…From another perspective, the distribution of RE atoms during the precipitation has been a scientifically interesting issue because the RE atoms substitute for certain atomic sites in the matrix lattice and form various sophisticated structures. A deep comprehension, especially an atomic‐scale one, of the precipitate structures paves the way for the related modeling and simulation that may trigger significant advancement in solid‐state physics …”
Section: Introductionmentioning
confidence: 99%